PROSPECTS FOR THE PARTICIPATION OF CIVIL SOCIETY IN THE DEFENSE OF THE STATE - Fedotova, Yuliya; Formakidov, Dmitry; Abdikeev, Niyaz; Moreva, Evgenia; Trifonov, Pavel (Revista Inclusiones, 2020)
The article discusses the prospects for the participation of civil society in the protection of the state and state interests. The legal foundations of such participation, its practice and the problems of formation and implementation in the Russian Federation and foreign countries are analyzed. The important role of the person’s active life position and his desire to participate in the affairs of society and the state for these legal relations is noted. The analysis of modern threats and dangers of national security and state interests of Russia and other countries is carried out. The interrelation of state, public interests and interests of the individual and the interdependence of the security of the individual, society and the state are revealed. The recognition that ensuring personal security can be considered a general legal principle imposes obligations, first of all, on state bodies, not only to observe the rights and freedoms of a person and a citizen in a passive form, which means abstinence from violations of rights and freedoms, but to take active actions that contribute to ensuring personal security.